The Evaluation of Plasma and Leukocytic IL-37 Expression in Early Inflammation in Patients with Acute ST-Segment Elevation Myocardial Infarction after PCI - Xin Wang; Xiangna Cai; Lan Chen; Duanmin Xu; Jilin Li (Mediators of Inflammation)
Objective. Acute ST-segment elevation myocardial infarction (ASTEMI) is accompanied by increased expression of inflammation and decreased expression of anti-inflammation. IL-37 was found to be involved in the atherosclerosis-related diseases and increased in acute coronary syndrome. However, the level of IL-37 in blood plasma and leukocytes from patients with ASTEMI after percutaneous coronary intervention (PCI) has not been explored. Methods. We collected peripheral venous blood from consented patients at 12 h, 24 h, and 48 h after PCI and healthy volunteers. Plasma IL-37, IL-18, IL-18-binding protein (BP), and high sensitive C reaction protein (hs-CRP) were quantified by ELISA and leukocytic IL-37 and ICAM-1 by immunoblotting. Results. Plasma IL-37, IL-18, and IL-18 BP expression decreased compared to those in healthy volunteers while hs-CRP level was high. Both leukocytic IL-37 and ICAM-1 were highest expressed at 12 h point but significantly decreased at 48 h point. Conclusion. These findings suggest L-37 does not play an important role in the systematic inflammatory response but may be involved in leukocytic inflammation in ASTEMI after PCI.